2023
DOI: 10.3390/ijms24032451
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Non-Neurogenic and Neurogenic Lower Urinary Tract Dysfunction (LUTD) in SCI-Induced and Partial Bladder Outlet Obstruction Mouse Models

Abstract: We examined bladder function following spinal cord injury (SCI) by repeated urodynamic investigation (UDI), including external urethral sphincter (EUS) electromyography (EMG) in awake restrained mice and correlated micturition parameters to gene expression and morphological changes in the bladder. A partial bladder outlet obstruction (pBOO) model was used for comparison to elucidate both the common and specific features of obstructive and neurogenic lower urinary tract dysfunction (LUTD). Thirty female C57Bl/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated that mice exhibited a series of immune-inflammatory reactions in bladder tissue following SCI, including cytokine-mediated signaling and production of interleukin-6. Furthermore, transcriptomic sequencing confirmed the upregulation of genes involved in immune response (CXCL13, SYK, and CCR7) and inflammation (CCR2, CX3CL1, and TREM2) ( Von Siebenthal et al, 2023 ). The KEGG analysis also revealed that circRNAs in NB tissue linked to SSCI were significantly enriched in pathways, such as the “IL-17 signaling pathway”, the “TGF-beta signaling pathway”, the “cAMP signaling pathway”, the “PI3K-Akt signaling pathway”, and the “MAPK signaling pathway”.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study demonstrated that mice exhibited a series of immune-inflammatory reactions in bladder tissue following SCI, including cytokine-mediated signaling and production of interleukin-6. Furthermore, transcriptomic sequencing confirmed the upregulation of genes involved in immune response (CXCL13, SYK, and CCR7) and inflammation (CCR2, CX3CL1, and TREM2) ( Von Siebenthal et al, 2023 ). The KEGG analysis also revealed that circRNAs in NB tissue linked to SSCI were significantly enriched in pathways, such as the “IL-17 signaling pathway”, the “TGF-beta signaling pathway”, the “cAMP signaling pathway”, the “PI3K-Akt signaling pathway”, and the “MAPK signaling pathway”.…”
Section: Discussionmentioning
confidence: 94%
“…This method may be used to reduce the possibility of long-term indwelling urinary catheters. Von Siebenthal et al [25] compared bladder function in the SCI (neurogenic) and bladder outlet obstruction (obstructive) mice by repeated urodynamic examination. This study found that the SCI group had dysfunctional bladder detrusor and sphincter and significantly increased bladder pressure 1 week after injury, and the bladder gradually developed fibrosis throughout the process.…”
Section: Mechanism Of Occurrencementioning
confidence: 99%
“…Characteristic changes include bladder wall thickening as a result of cellular hypertrophy and hyperplasia [4], as well as enhanced deposition and turnover of extracellular matrix (ECM) leading to fibrosis [5, 6]. With the advent of genome-wide expression profiling, several groups have begun to characterize the molecular landscape that underlies the response of the bladder to spinal cord damage in animal models [710] and in smooth muscle cells isolated from human bladder biopsies [11, 12]. In addition to verification of altered expression of ECM proteins and regulators, microarray-based expression profiling of bladder tissue from spinal cord injured rats also provided important insights into additional drivers of neurogenic bladder pathophysiology including the pro-fibrotic regulator TGFβ1 and pro-inflammatory mediators such as IL1β and S100A8/A9 [7, 8].…”
Section: Introductionmentioning
confidence: 99%